Drug Target Engagement Using Coupled Cellular Thermal Shift Assay—Acoustic Reverse-Phase Protein Array. (February 2020) - Herledan, Adrien; Andres, Marine; Lejeune-Dodge, Aurore; Leroux, Florence; Biela, Alexandre; Piveteau, Catherine; Warenghem, Sandrine; Couturier, Cyril; Deprez, Benoit; Deprez-Poulain, Rebecca
In the last 5 years, cellular thermal shift assay (CETSA), a technology based on ligand-induced changes in protein thermal stability, has been increasingly used in drug discovery to address the fundamental question of whether drug candidates engage their intended target in a biologically relevant setting. To analyze lysates from cells submitted to increasing temperature, the detection and quantification of the remaining soluble protein can be achieved using quantitative mass spectrometry, Western blotting, or AlphaScreen techniques. Still, these approaches can be time- and cell-consuming. To cope with limitations of throughput and protein amount requirements, we developed a new coupled assay combining the advantages of a nanoacoustic transfer system and reverse-phase protein array technology within CETSA experiments. We validated the technology to assess engagement of inhibitors of insulin-degrading enzyme (IDE), an enzyme involved in diabetes and Alzheimer's disease. CETSA—acoustic reverse-phase protein array (CETSA-aRPPA) allows simultaneous analysis of many conditions and drug–target engagement with a small sample size, in a rapid, cost-effective, and biological material-saving manner.